Formaldehyde : exposure, toxicity and health effects - Zhang, Luoping (Issues in toxicology, 2018)
This book consolidates current knowledge of all aspects of formaldehyde from exposure to genotoxicity and from epidemiological case studies to adverse health outcomes.